Investigation of Magnetic Iron Oxide Nanoparticle Properties with Coprecipitation Methods Under Different Reaction Conditions - Salgın, Sema; Salgın, Uğur; Soyer, Nagihan (Nanoscience & Nanotechnology-Asia, 2021)
Objective: In this study, magnetic iron oxide nanoparticles were synthesized by cost effective and an easy co-precipitation method. Methods: The effects of reaction parameters such as the mole ratio of Fe2+/Fe3+ (1/1, 1/2 and 1/3) and the base type (NaOH and NH4OH) on the average hydrodynamic diameter, zeta potential, chemical and morphological structure and saturation magnetization values of magnetic iron oxide nanoparticles were systematically investigated. Results: Magnetic iron oxide nanoparticles synthesized at the mole ratio of 1/2 using NH4OH base gave better results in terms of particle size and particle shape, magnetization value. Conclusion: In order to prevent the formation of different phases in the co-precipitation method, an alternative approach was developed and the reaction was performed using inert supercritical CO2 atmosphere.
Keywords: zeta potential